A pilot study of a virtually delivered dissonance-based eating disorder prevention program for young women with type 1 diabetes: within-subject changes over 6-month follow-up. - Wisting, Line; Haugvik, Severina; Wennersberg, Anne Louise; Hage, Trine Wiig; Stice, Eric; Olmsted, Marion P.; Ghaderi, Ata; Brunborg, Cathrine; Skrivarhaug, Torild; Dahl-Jørgensen, Knut; Rø, Øyvind (Eating Disorders)
Introduction: In an uncontrolled study, we previously demonstrated the feasibility and preliminary efficacy of our virtual diabetes-specific version (Diabetes Body Project) of the eating disorder (ED) prevention program the Body Project. The aim of the current study was to evaluate further this program for women with type 1 diabetes (T1D) by assessing within-subject changes in outcomes from pretest over 6-month follow-up. Methods: Young women with T1D aged 16–35 years were invited to participate in Diabetes Body Project groups. A total of 35 participants were allocated to five Diabetes Body Project groups (six meetings over 6 weeks). Primary outcome measures included ED risk factors and symptoms, and secondary outcomes included three T1D-specific constructs previously found to be associated with ED pathology: glycemic control as measured by HbA1c level, diabetes distress, and illness perceptions. Results: Within-subject reductions, with medium-to-large effect sizes, were observed for the primary (ED pathology, body dissatisfaction, thin-ideal internalization, and appearance ideals and pressures) and secondary outcomes (within-condition Cohen's ds ranged from.34 to 1.70). Conclusion: The virtual Diabetes Body Project appears to be a promising intervention worthy of more rigorous evaluation. A randomized controlled trial with at least a 1-year follow-up is warranted to determine its efficacy compared to a control condition.